2016
DOI: 10.1002/chem.201601224
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular Tetrylene Lewis Adducts: Synthesis and Reactivity

Abstract: A series of benzyl(diphenylphosphino) and o-phenyl(diphenlyphosphino) substituted germylenes and plumbylenes were synthesized by nucleophilic substitution between the respective lithium reagent and tetrylene halide. The Lewis pairs were characterized by X-ray crystallography and NMR spectroscopy. The reactivity of the tetrylenes was investigated with respect to azide addition. In the germylene case, the germaniumimide was formed as the kinetically controlled product, which rearranges upon heating to give the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 115 publications
5
48
0
Order By: Relevance
“…[4e, 10] TheB ÀGeÀHs tructural motive is known in the literature from BH 3 adducts with germylene hydrides and products of the oxidative addition of aB À Hb ond of Me 3 NBH 3 at ag ermylene. [1l, 11] In these structures,t he B À Ge distances [2.15(7)-2.064 (6) ]a re comparable to the found value of 4.…”
Section: Angewandte Chemiesupporting
confidence: 77%
See 1 more Smart Citation
“…[4e, 10] TheB ÀGeÀHs tructural motive is known in the literature from BH 3 adducts with germylene hydrides and products of the oxidative addition of aB À Hb ond of Me 3 NBH 3 at ag ermylene. [1l, 11] In these structures,t he B À Ge distances [2.15(7)-2.064 (6) ]a re comparable to the found value of 4.…”
Section: Angewandte Chemiesupporting
confidence: 77%
“…[5] Therefore, additions of alkynes,olefins,and azides with Group 14 Lewis pairs were studied. [6] We found that the E ! P( E= Ge,S n) bond displays distinct reactivity,w hich adds to small molecules under ring expansion.…”
mentioning
confidence: 83%
“…A recent report of similar reactivity describes alkene insertion into the Si−Si‐bond of the stable acyclic silylene dipp(Me 3 Si)N−Si−Si(SiMe 3 ) 3 (dipp=2,6‐ i Pr 2 C 6 H 3 ) . Examples of alkyne insertion into the Sn−P and Ge−P bonds of stannylene/germylene–phosphine adducts were reported by Wesemann and co‐workers …”
Section: Introductionmentioning
confidence: 64%
“…[9] Examples of alkyne insertion into the SnÀPa nd GeÀPb onds of stannylene/germylene-phosphinea dducts were reported by Wesemann and co-workers. [10,11] The present study deals with two aspects of germylene chemistry: 1) the importance of Lewis base-germylenea dducts, which either isomerize or dimerize in the absence of as uitable donor, and the fact that weak phosphane bases can be exchanged easily for stronger basess uch as NHCs or isocyanides. 2) am echanistic rationalef or the alkyne-insertion reactions, concludingthat adduct formation can act as ad riving force for the isomerization reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, geminal P/Al [3] and P/B [4,5] Lewis pairs have attracted considerable interestq uite recently due to their remarkable activity in the activation of small molecules. In addition, other geminal FLPs based on N/B, [6] N/Al, [7] P/X [8] (X = Group 14 element), and even P/Ga [9] have been prepared in order to tune the Lewis acidity/basicity of the FLP antagonists and consequently,t om odify the activity of the system. Despite that, the influence of the nature of the Lewisp airs on the reactivity of the FLP is so far not fully understood, which is of crucial importance for furtherd evelopment of FLPs.…”
Section: Introductionmentioning
confidence: 99%